2021
DOI: 10.15244/pjoes/128110
|View full text |Cite
|
Sign up to set email alerts
|

Study on Evaluation of Ecological Environment Quality and Temporal-Spatial Evolution of Danjiang River Basin (Henan Section)

Abstract: The Danjiang River Basin (Henan Section) is the water source of the Middle Route of the South-to-North Water Transfer Project. Its ecological environment quality has received increasing attention. In this study, on the basis of the ecological environment of the study area, we constructed the evaluation index system from four aspects: ecological basis, ecological structure, ecological stress and ecological benefits. The variable fuzzy set model was improved by using the central point triangle whitening weight f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Overall, it presented a pattern of low in the central area and high in the surrounding areas. Furthermore, the trend analysis based on the RSEI data for the 21 periods showed that 63.97% of the area exhibited a upward trend in the future ecological environment quality of Luoyang city, aligning with previous research findings [44].…”
Section: The Spatiotemporal Variation Characteristics Of Rseisupporting
confidence: 88%
“…Overall, it presented a pattern of low in the central area and high in the surrounding areas. Furthermore, the trend analysis based on the RSEI data for the 21 periods showed that 63.97% of the area exhibited a upward trend in the future ecological environment quality of Luoyang city, aligning with previous research findings [44].…”
Section: The Spatiotemporal Variation Characteristics Of Rseisupporting
confidence: 88%
“…In the previous literature, human engineering activities have caused serious damage to the ecological environment, such as coal mining (Liu et al, 2023), urban sprawl (Lin et al, 2022), and climate rise caused by excessive carbon dioxide emissions (Zhang et al, 2023). However, with the strict implementation of laws, regulations and policies such as ecological environmental protection, the quality of the ecological environment has a tendency to improve (Wang et al, 2021).…”
Section: Figure 10mentioning
confidence: 99%
“…The NDBSI commonly expresses the DI. The SI, IBI, and NDBSI can be determined using Equations ( 5), ( 6) and (7), respectively [14,15].…”
Section: Construction Of the Rseimentioning
confidence: 99%
“…Effective scientific monitoring and quantitative evaluation of the urban EEQ are crucial for protecting the urban EE, harmonious development between human beings and nature, and the sustainable development of society [5]. Remote sensing technology has become an essential tool for monitoring and assessing EEQ due to its wide range of information acquisition, real-time monitoring, high precision, convenience, objectivity, large-scale coverage, rapidity, and periodicity [6][7][8][9]. In practice, remote sensing technology has been extensively applied in EE monitoring and evaluation.…”
Section: Introductionmentioning
confidence: 99%